Online Gold Dropship in Shopee Application Under Perspective Indonesian Ulama Council of North Sumatera - Sartika Khairani Siregar; Abbas Arfan (Journal of Islamic Business Law, 2017)
The seller in the shopee application is given various features of the dropship feature that can be easily accessed by the dropshipper to run their business by getting items they want to resell on social media. This research was conducted to determine the law of buying and selling gold by dropship in the opinion of the Indonesian Ulama Council (MUI) of North Sumatra province. This research is classified into doctrinal law research type. This research is called field research and sociological law research. The approach used is a sociological juridical approach and conceptual approach. the gold dropship mechanism in the shopee application has several stages that must be passed by the dropshipper to be able to get the desired gold and directly sent to the buyer by including the dropshipper's identity as the sender and not the identity of the gold owner. There is no relationship between the gold owner in the shopee app and the dropshipper who don't even know each other. Transactions that occur between the two are only buying and selling transactions. According to the Indonesian Ulama Council (MUI) of North Sumatra province, the gold dropship transaction in the shopee application is unlawful. This is because gold is ribawi amwal which has special treatment if it is used as an object of buying and selling. Legitimate buying and selling of gold is done face-to-face and cash.